2022
DOI: 10.1091/mbc.e21-10-0507
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 threatens faculty diversity: postdoctoral scholars call for action

Abstract: Despite substantial investment and effort by federal agencies and institutions to improve the diversity of the professoriate, progress is excruciatingly slow. One program that aims to enhance faculty diversity is the Institutional Research and Academic Career Development Award (IRACDA) funded by the National Institutes of Health/National Institute of General Medical Sciences. IRACDA supports the training of a diverse cohort of postdoctoral scholars who will seek academic research and teaching careers. The San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, while we are barely out of the COVID-induced disruptions, there are some glimpses of positive changes that are emerging ( Gardner et al, 2021 ; Gould, 2021 ; Shah et al, 2021 ). For example, in order to mitigate isolation and perpetuate a learning environment when labs shut down in early 2020, institutional entities responsible for professional skill-building and career-promoting programming pivoted to remote platforms with some interesting outcomes ( Andrade et al, 2022 ). Remote sessions now appear to be not only acceptable, but may even be preferred by trainees, as they are more accessible, provide more efficient use of time and offer flexibility (such as having the possibility to watch recorded sessions later).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while we are barely out of the COVID-induced disruptions, there are some glimpses of positive changes that are emerging ( Gardner et al, 2021 ; Gould, 2021 ; Shah et al, 2021 ). For example, in order to mitigate isolation and perpetuate a learning environment when labs shut down in early 2020, institutional entities responsible for professional skill-building and career-promoting programming pivoted to remote platforms with some interesting outcomes ( Andrade et al, 2022 ). Remote sessions now appear to be not only acceptable, but may even be preferred by trainees, as they are more accessible, provide more efficient use of time and offer flexibility (such as having the possibility to watch recorded sessions later).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the pandemic on postdocs is not unlike the severe and far-reaching effects observed throughout the biomedical workforce, such as significant job losses, educational disparities, and elevated mental health issues ( Levine et al, 2021 ; Jagsi et al, 2021 ; Gao et al, 2021 ; Doyle et al, 2021 ; Korbel and Stegle, 2020 ; Carr et al, 2021 ; Yan, 2020 ; Servick et al, 2020 ; Andrade et al, 2022 ; Myers et al, 2020 ). Although the financial impact of COVID-19 on scientific productivity has not yet been fully realized, the National Institutes of Health (NIH) estimates a $16 billion loss because of delayed research, and the Bureau of Labor Statistics reported the largest decline in college and university employment since the 1950s ( Baumann, 2021 ; Bauman, 2021 ; Bauman, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sadly, the COVID-19 pandemic and coinciding urgency for social reform has exacerbated existing disparities. These disparities include increased demand for service on committees, household and caregiving responsibilities for women, and lack of mentorship and sponsorship [5,6]. To ensure we do not lose a generation of • What type of security will you need for your data?…”
Section: Supporting Diverse Junior Facultymentioning
confidence: 99%
“…Increases in the cost of living due to the pandemic threaten to derail recruitment of faculty from groups historically excluded from science [5]. Under-represented minority scientists are more likely to be under-resourced financially and therefore disproportionately impacted by unsustainable financial hardship from the pandemic, such as loss of spousal income, increased cost of living, and lack of affordable housing.…”
Section: Communicationmentioning
confidence: 99%